Is local bias a cross-border phenomenon? Evidence from individual investors’ international asset allocation - Baltzer, Markus; Stolper, Oscar; Walter, Andreas (Journal of Banking & Finance, 2013)
Extant literature consistently documents that investors tilt their domestic equity portfolios towards regionally close stocks (local bias). We hypothesize that individual investors’ local bias is not limited to the domestic sphere but instead also determines their international investment decisions. Our results confirm the presence of a cross-border local bias. Specifically, we show (i) that the stockholdings of individual investors living within regional proximity to a foreign country display a significantly lower foreign investment bias towards investment opportunities in that country and (ii) that this drop in foreign investment bias levels is disproportionately driven by investments in regionally close neighbor-country companies. The impact of cross-border local bias on investors’ bilateral foreign equity investments is economically significant and holds even after controlling for previously identified explanations of international asset allocation.